Dampak Kebijakan: (Studi Kasus pada Pemungutan Suara Ulang (PSU) Pemilihan Kepala Daerah dan Wakil Kepala Daerah Kota Pekanbaru Tahun 2011) - M. Tinov; Raja Amin; Auradian Marta (Nakhoda: Jurnal Ilmu Pemerintahan, 2013)
The research problem in this study was initiated with the interim decision of the Constitutional Court No. 63/PHPU.D-IX/2011 which basically instruct the Regional Election Commission ( ElectionCommission ) to implement the Pekanbaru City Ballot Re ( PSU ) in all regions of the city of Pekanbaru . Therefore, this study sought to describe the impact of the issuance of the policy is for interested parties . This study used a qualitative approach to the sources of information and data obtained from in-depth interviews of infroman research and study documentation . This study obtain the result that the Constitutional Court policies impact not only to the policy target group RegionalElection Commission of Pekanbaru , but also impacts outside the target groups such as the mutation of the Civil Service in the local government area in Pekanbaru . Then the impact of other policies are costs to be borne either by the government or indirectly by the public costs of delays Voting Re-Election of Regional Head and Deputy Head of Pekanbaru .